Predicting students’ intentions for post-COVID-19 face-to-face classes - Quah, Wei Boon; Gopal, Krishnavehni (International Journal of Evaluation and Research in Education (IJERE), 2025)
The COVID-19 pandemic led to community college closures, with reopening being considered as a potential strategy to enhance learning outcomes. However, existing literature lacks insights into the factors that determine students’ intention to attend limited face-to-face classes. To address this gap, a study was conducted to explore the intentions of 122 English students at a Malaysian community college regarding attendance in such classes post-reopening, using the theory of planned behavior as a framework. Results indicated a moderate level of intention to attend. Perceived behavioral control (PBC) and subjective norm positively predicted students’ intentions, while attitude did not significantly contribute. These findings highlight the critical role of PBC and subjective norms in shaping students’ intentions. As many community colleges prepare for phased reopening, understanding students’ diverse perspectives is crucial for informed decision-making regarding in-person instruction. Institutions must consider these factors to gain nuanced insights into students’ inclinations towards face-to-face classes, thereby facilitating effective planning amidst ongoing uncertainties.